Cartographing street homes: preliminary maps of a city that is not seen - Schulze, Carolina; Hoepers Preve, Ana Maria (Geografares, 2014)
The text shows the movement of a research in education and geography that is based on the concept of maps and cartography intensive to try, once again, the variation of Cartesian lines that attach to the quality of truth maps of the territory represented. The first learning about building houses, on how to invent a place for themselves in the city known, also sets in motion the notion that multiple cities every city behaves, housing weaving a city that is not seen. The maps produced and presented in the text and express experience, like the homeless, and mobility variations. Its lines have density, are made of life.Keywords: street cartographies; city that is not seen; geography and education.